2022
DOI: 10.3390/su14052927
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Orbital and Meltwater Climate Forcings on the Southern Ocean Dynamics during the Last Deglaciation

Abstract: The last deglacial climate evolution, from 19 to 9 thousand years before the present, represents the vital role of feedback in the Earth’s climate system. The Southern Ocean played a fundamental role by exchanging nutrients and carbon-rich deep ocean water with the surface during the last deglaciation. This study employs a fully coupled Earth system model to investigate the evolution of Southern Ocean dynamics and the roles of changes in orbital and meltwater forcings during the last deglaciation. The simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 99 publications
(192 reference statements)
1
5
0
Order By: Relevance
“…We found that the average and maximum mixed layer depth vary coherently with a Pearson correlation coefficient of 0.89 (p = 0) (Figure 1e,f). The mixed layer depth decreased during the HS1 and YD periods, which indicates reduced deep convection and a weakened AMOC strength (Figure 1g), which is in agreement with previous studies [10][11][12][13]. The reduction in the AMOC strength weakened the upper meridional overturning cell, inducing a bipolar seesaw response [11], and it reduced the northward meridional heat transport.…”
Section: Resultssupporting
confidence: 90%
“…We found that the average and maximum mixed layer depth vary coherently with a Pearson correlation coefficient of 0.89 (p = 0) (Figure 1e,f). The mixed layer depth decreased during the HS1 and YD periods, which indicates reduced deep convection and a weakened AMOC strength (Figure 1g), which is in agreement with previous studies [10][11][12][13]. The reduction in the AMOC strength weakened the upper meridional overturning cell, inducing a bipolar seesaw response [11], and it reduced the northward meridional heat transport.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have shown that the melting of Antarctic sea ice releases freshwater, which increases the buoyancy of Southern Ocean upwelled water (Iudicone et al, 2008) and strengthened the upper limb of the ocean meridional overturning circulation (Abernathey et al, 2016;Saenko et al, 2002). Furthermore, numerical simulations have confirmed the importance of freshwater fluxes in determining changes in Southern Ocean upwelling during the last deglacial period (Mandal et al, 2021;Mandal et al, 2022;Morrison et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…The paleoclimatology community recognizes that the Southern Ocean overturning circulation is primarily driven by wind (Anderson et al, 2009;Menviel et al, 2018). Several studies, however, have found that changes in buoyancy flux caused by freshwater discharge (Abernathey et al, 2016;Liu et al, 2021), ocean eddies (Lauderdale et al, 2017), topography (Liu et al, 2021), and Antarctic sea ice feedback (Ferrari et al, 2014;Jansen & Nadeau, 2016;Mandal et al, 2021;Mandal et al, 2022;Marzocchi & Jansen, 2017;Stein et al, 2020) contribute to the Southern Ocean dynamical changes during the most recent deglacial period. As a result, it is critical to comprehend the role of Antarctic sea ice in surface buoyancy flux, which influences the Southern Ocean overturning circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications employing the TraCE-21ka experiment model simulations have highlighted the relationship between Antarctic sea ice and SO processes [7,9,10]. The SO upwelling was made stronger by an increase in freshwater discharge brought on by Antarctic sea ice melting [6,10].…”
Section: Discussionmentioning
confidence: 99%
“…Paleoclimate scientists acknowledge the SO overturning circulation to be predominantly wind-driven [4,5]. However, numerous studies have demonstrated that variations in buoyant flux caused by freshwater outflow [6,7], ocean eddies [8], topography [7], and Antarctic sea ice feedback [9][10][11][12][13][14] contribute to the SO dynamical changes during the last deglacial time. Therefore, understanding how the distribution of Antarctic sea ice affects the surface distribution and transport of AAIW and SAMW movement is crucial.…”
Section: Introductionmentioning
confidence: 99%